2015
DOI: 10.1038/npp.2015.49
|View full text |Cite
|
Sign up to set email alerts
|

CRF2 Receptor Deficiency Eliminates the Long-Lasting Vulnerability of Motivational States Induced by Opiate Withdrawal

Abstract: Vulnerability to stressful life events is a hallmark of drug dependence that may persist long after cessation of drug intake and dramatically fuel key clinical features, such as deregulated up-shifted motivational states and craving. However, to date, no effective therapy is available for reducing vulnerability to stressful events in former drug users and drug-dependent patients, mostly because of poor knowledge of the mechanisms underlying it. In this study, we report that genetic inactivation of the stress-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…Indeed, stress exposure is considered a major risk factor for relapse to substance intake in former substance users (Sinha, 2001). Accordingly, laboratory animal studies showed that physical, psychological or pharmacological stressors reinstate substance-seeking behaviour and induce negative affective-like states, even after relatively long periods of substance withdrawal (Shaham et al, 2003;Blatchford et al, 2005;Breese et al, 2005;Morisot et al, 2015). The present results extend to social behaviour the deleterious consequences of substance withdrawal and the associated long-lasting vulnerability to stress.…”
Section: Figuresupporting
confidence: 60%
“…Indeed, stress exposure is considered a major risk factor for relapse to substance intake in former substance users (Sinha, 2001). Accordingly, laboratory animal studies showed that physical, psychological or pharmacological stressors reinstate substance-seeking behaviour and induce negative affective-like states, even after relatively long periods of substance withdrawal (Shaham et al, 2003;Blatchford et al, 2005;Breese et al, 2005;Morisot et al, 2015). The present results extend to social behaviour the deleterious consequences of substance withdrawal and the associated long-lasting vulnerability to stress.…”
Section: Figuresupporting
confidence: 60%
“…In this sense, several evidences points to a role of amygdala CRF 2 receptors of rodents in the modulation of anxiety related to the withdrawal syndrome and the preference for consumption. For example, Morisot et al (2015) revealed that GABA biosynthesis within the amygdala of mice after opiate withdrawal requires functional CRF 2 receptors. Orozco-Cabal et al (2008), using an electrophysiological approach, showed a synergism between D1-like dopamine receptors and CRF 2 receptors in BLA-to-medial prefrontal cortex synaptic transmission in rats subjected to repeated cocaine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Stress-induced reinstatement following abstinence is a feature of abuse for multiple classes of drugs. While the role of CRF in the VTA has been explored relative to depressants such as morphine and ethanol, [23][24][25] it has also been studied for its role in stress-induced cocaine seeking. 26 The most important source of CRF in the VTA for cocaine reinstatement is likely from neurons in the bed nucleus of the stria terminalis, 27 although other inputs such as the lateral hypothalamic area and paraventricular hypothalamic nucleus could also play a F I G U R E 4 Repeated cocaine and methamphetamine injections increase CRF2 signal and decrease astrocyte number in the VTA and SN.…”
Section: Crf2 In the Vta And Snmentioning
confidence: 99%